Macroeconomic implications and growth regimes under alternative interpretations of household debt - Emilia G. Marsellou (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2022)
This paper attempts to contribute to the ongoing literature that relates consumer debt to income inequality. The most prevalent interpretation of consumer debt is working households' emulation of upper classes' consumption patterns or horizontal consumption emulation reminiscent of 'keeping up with the Joneses'. This paper suggests an alternative link between consumer debt and income inequality: working households borrow to sustain their established standard of living. Furthermore, the borrowing function used allows the examination of alternative working households' borrowing behaviours. The findings suggest that massive borrowing triggered by income inequality can be sustainable under high rates of economic growth. Also, cross-scenario comparisons show that different borrowing behaviours have both quantitative and qualitative effects on the short and the long run, in the growth regime and in macroeconomic stability.
Keywords: 330; consumer borrowing; inequality; growth regime; macroeconomic stability; simulationE120; E210; E250; E440; E470; O410